Coexpression of rumen fungal xylanase and bifunctional cellulase genes in Escherichia coli - Comlekcioglu,Ugur (2017)
ABSTRACT Rumen fungi inhabit the gastro-intestinal tract of ruminants and the most non-ruminant herbivores. Rumen fungi produce highly active plant cell wall degrading enzymes, therefore they have gained scientific interest. In this study, genes encoding xylanase (xynA-7) and cellulase (celA-5) were amplified from Neocallimastix sp. GMLF7 and Orpinomyces sp. GMLF5, respectively, and expressed in Escherichia coli. XynA-7 was found to be active only on xylan, however CelA-5 had activity both on carboxymethyl cellulose and lichenan. Lichenase activity of CelA-5 was found to be higher than carboxymethyl cellulase activity. The optimal conditions were at pH 6.0 and 40 °C for CelA-5 and at pH 6.5 and 50 °C for XynA-7. A coexpression vector was constructed to coproduce the XynA-7 and CelA-5 and then transformed into E. coli. The ability of the transformed E. coli strain to produce CMCase, xylanase and lichenase was evaluated. The transformed E. coli strain acquired the capacity to degrade CMC, xylan and lichenan.